Five-year evaluation of bone health in liver transplant patients: developing a risk score for predicting bone fragility progression beyond the first year - Abate, Ejigayehu G.; McKenna, Amanda; Yang, Liu; Ball, Colleen T.; Kearns, Ann E. (Frontiers in Endocrinology, 2025)
IntroductionLiver transplant (LT) recipients have a substantial risk of bone loss and fracture. An individual’s risk is highest before and within the first year after transplantation and returns to baseline in some patients but not all. We aim to identify risk factors for bone loss and fracture beyond the first year LT and to create a risk-scoring tool to aid clinicians in identifying those at high risk for bone loss and fracture.MethodsWe conducted a retrospective review of 264 liver transplant recipients between 2011 and 2014, who were followed in our transplant clinic for an additional five years. Clinical records were evaluated at the one-year post-LT visit and subsequently on an annual basis for up to five years.ResultsOver a median follow-up of 3.6 years post-liver transplantation, 40 out of 264 patients experienced disease progression, defined as worsening bone mineral density (BMD), initiation of osteoporosis treatment, or a new fracture. Factors associated with BMD progression included female sex, Caucasian race, new fractures, number of acute rejection events requiring treatment, and lower dual energy X-ray absorptiometry (DXA) scores after the first year post-LT. A risk model was developed using multivariable analysis, with a risk score based on BMD categories. The concordance index was 0.771, indicating good discrimination between those who progressed and those who did not. Risk categories were defined as low (0-4 points), medium (5 points), and high (6-9 points) based on model coefficients. The probability of progression-free survival at two years post-LT was 96.7% for low-risk, 83.1% for medium-risk, and 59.1% for high-risk groups.ConclusionWe developed a simple, clinically applicable risk score that predicts bone disease progression beyond the first year after LT. This tool may help guide appropriate bone health follow-up, although prospective validation is necessary.